Enhancing Parenting Quality through a Mobile Learning-Based Parenting Program - Ayu, Indri (Journal of Childhood Development, 2025)
The widespread use of WhatsApp in parenting learning processes today is a highly intriguing phenomenon. Parents learn a great deal from social media and chat applications about parenting techniques. Ideally, this should help improve the quality of parenting in the digital era, though there are also challenges and drawbacks. Based on this background, the purpose of this study is to examine mobile learning-based parenting education in terms of program meaningfulness and parenting quality. This study employs a descriptive quantitative approach, involving 55 participants. Data were collected through a questionnaire created using Google Forms. The findings reveal that the accumulation of messages in WhatsApp groups reduces participant engagement; however, it also improves relationships with their spouses and children at home. The parenting quality of participants was categorized as "very high," while their participation level was categorized as "high." Partially, participation has an influence of 25.6%, while the simultaneous influence of participation and program meaningfulness on parenting quality is 28%. This study contributes to the growing body of knowledge on digital-era parenting by providing empirical evidence of the effectiveness of mobile learning-based programs in enhancing parenting quality. It highlights both the opportunities and limitations of using WhatsApp as a platform for parenting education, offering insights for future program development and implementation.